Post Covid-19 Pandemic Economic Growth With Human Capital As A Long Term Drive - Lambok DR Tampubolon (Universitas Udayana, 2024)
The latest direction in development economics research both at home and abroad is starting toreduce the use of convoluted analytical models. Using too many variables but with unclearcausality will actually complicate the analysis and produce results that are not necessarily goodand correct. There are quite a lot of scientific work findings that use dozens of variables, withstatistically significant results, but if you examine the relationship many questions arise such as